Comunicación corporativa y mediación social en un entorno globalizado - Cabada del Río, Marina (Mediaciones Sociales, 2008)
Current businesses operate in the socio-economic environment adopting its pro-social conduct ; Which is then reflected in the communication process This happens in a new ideological frame of Social Welfare which gradually eclipses the ideology of illimited progress that prevailed during the first era of business development In the current consumption society ; However ; Corporate communication developed under marketing factors ; Sometimes translates into the consumption of values Great corporate monsters ; -“predators” of the 21st century- start to use up not only the Planet’s natural resources ; But also its cultural resources We need to observe the erosion suffered by the movements ; Values and social problems due to a constant instrumentalization within an environment of consumerism These are used in advertisements as solidarity hooks to sell.
Keywords: Social mediation; Corporate communication; Marketing; Consumption society; Solidarity